Implementasi Tugas Hakim Pengawas Dan Pengamat Terhadap Pelaksanaan Putusan Pengadilan Pada Lembaga Pemasyarakatan Di Indonesia - Robertho Sohilait; Deassy Jacomina Anthoneta Hehanussa; Juanrico Alfaromona Sumarezs Titahelu (Program Studi Hukum Diluar Kampus Utama Universitas Pattimura Kabupaten Maluku Barat Daya, 2023)
The institution of supervisory judges and observers is a new institution that was born with the enactment of Law No. 8 of 1981 concerning the Criminal Procedure Code. The task of supervision and observation is very important, considering that its duties are not only related to convicts who have been sentenced, but also to convicts who have finished serving their sentences with the aim that there is a guarantee that the decisions handed down by the court are carried out properly. Purposes of the Research: The type of research used is normative legal research using a statute approach, a conceptual approach, and a case approach. While the sources of legal materials used are primary legal materials, secondary legal materials and tertiary legal materials. Results of the Research: From the results of the study, it is explained that supervisory judges and observers are very relevant in the implementation of the current criminal justice system because with the presence of supervisory judges and observers they can carry out direct supervision and observation of court criminal decisions that have legal force and can directly assess whether the decision can be useful. for prisoners or not so that when he is ready to return to the midst of society so that the purpose of the criminal justice system that corrects the perpetrators can be realized, but as long as in Indonesia the implementation of the rights of supervisors and observers is not carried out properly, this is due to the absence of strict sanctions to judges and courts, the lack of regulations and provisions regarding supervisory and observer judges, as well as supervisory and observer judges can be considered as interfering formally with the authority of the penitentiary, therefore the cooperation of the ministry of law is required. and human rights and the judiciary to formulate new regulations for supervisory and observer judges.